Pengembangan Lms Berbasis PBL Untuk Meningkatkan Critical Thinking Pada Elemen Algoritma Pemrograman Siswa SMK - Fadila Novitasari; Muhammad Sonhaji Akbar (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aims to develop a web-based Learning Management System (LMS) integrated with the Problem-Based Learning (PBL) model in the Algorithm and Programming element to test its feasibility, student critical thinking improvement, and student responses at SMKS Rajasa Surabaya. The research and development (R&D) method was applied using the ADDIE development model (Analyze, Design, Develop, Implement, Evaluate). The subjects consisted of 28 tenth-grade students of Computer and Network Engineering (TKJ) 1 using a One Group Pretest-Posttest Design. Data collection instruments included expert validation sheets, cognitive pretest-posttest, and student response questionnaires. Data were analyzed using percentage descriptive statistics, Shapiro-Wilk normality test, Wilcoxon Signed-Rank Test, and N-Gain test. Results indicated that: (1) The Moodle-based LMS achieved high validity from material experts (92.5%), test item experts (94%), lesson plan/RPM experts (92.85%), and media experts (90%); (2) There was a significant improvement in students' critical thinking skills, with average scores increasing from 54.24 to 82.63 (Asymp. Sig. 0.000 < 0.05) and an average N-Gain of 0.6174 (medium category); (3) Student response achieved 82.62% (very good category). Thus, the developed LMS is feasible and effective in enhancing critical thinking skills.